Effects of torsion on the behavior of peripheral steel-braced frame systems. - Erduran, Emrah (Earthquake engineering & structural dynamics.)
In this study, the torsional response of buildings with peripheral steel-braced frame lateral systems is evaluated. A three-dimensional model of a three story braced frame with various levels of eccentricity is created and the effects of torsion on the seismic response is assessed for four hazard levels. The response history analysis results indicate that, unlike frame structures, the torsional amplifications in the inelastic systems exceed those of corresponding elastic systems and tend to increase with an increase in the level of inelasticity. The ability of two simplified procedures, elastic response spectrum analysis and pushover analysis, to capture the torsional amplifications in steel-braced frames is evaluated.